2015
DOI: 10.1111/pai.12433
|View full text |Cite
|
Sign up to set email alerts
|

Fast food consumption in pregnancy and subsequent asthma symptoms in young children

Abstract: These findings suggest that in utero exposure to frequent fast food through maternal diet may be a risk factor for asthmatic symptoms in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…Fast foods, first popularized in the 1950s in America, are typically foods sold in restaurants or stores with preheated or precooked ingredients and served to customers in a packaged form for takeaway . Fast foods are typically calorically dense, high in refined carbohydrates, sodium, sugar, cholesterol, additives such as preservatives and colourants, with high concentrations of saturated fat . Hence, it has been hypothesized that the consumption of fast foods may exacerbate the development and progression of asthma and allergic diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast foods, first popularized in the 1950s in America, are typically foods sold in restaurants or stores with preheated or precooked ingredients and served to customers in a packaged form for takeaway . Fast foods are typically calorically dense, high in refined carbohydrates, sodium, sugar, cholesterol, additives such as preservatives and colourants, with high concentrations of saturated fat . Hence, it has been hypothesized that the consumption of fast foods may exacerbate the development and progression of asthma and allergic diseases .…”
Section: Introductionmentioning
confidence: 99%
“…4 Fast foods are typically calorically dense, high in refined carbohydrates, sodium, sugar, cholesterol, additives such as preservatives and colourants, with high concentrations of saturated fat. 5 Hence, it has been hypothesized that the consumption of fast foods may exacerbate the development and progression of asthma and allergic diseases. 6 However, the data available to date are heterogeneous, with some, but not all studies, reporting that asthma and allergic diseases are associated with the consumption of fast foods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the prenatal consumption of a Western diet can explain the increased prevalence of childhood wheezing illnesses in developed countries [3, 7, 8]. Indeed, numerous studies have shown a relationship between in utero exposure to certain maternal nutrients, food groups, or dietary patterns with a decreased or increased risk of these diseases.…”
Section: Maternal Dietmentioning
confidence: 99%
“…Indeed, numerous studies have shown a relationship between in utero exposure to certain maternal nutrients, food groups, or dietary patterns with a decreased or increased risk of these diseases. In a retrospective cohort study in the United States, von Ehrenstein et al found a dose-dependent association of fast food consumption during pregnancy and asthma risk at age 3.5 years [7]. Because this study assessed fast food consumption during pregnancy between 3–6 months after delivery, recall bias is a possibility.…”
Section: Maternal Dietmentioning
confidence: 99%
“…The results of the study by von Ehrenstein et al. suggest that frequent maternal consumption of fast food during pregnancy may increase their offspring's risk for asthmatic symptoms in early childhood. These findings were based on the authors’ prospective, population‐based study of 1201 mother/child pairs in Los Angeles, California, in which information about maternal prenatal fast‐food intake and other dietary, lifestyle, or environmental factors in pregnancy was assessed shortly after the women gave birth, and about 3 years later, the ISAAC core questions were used to assess wheeze/asthma and rhinitis symptoms in offspring.…”
Section: Fast‐food Consumption In Pregnancy and Subsequent Asthma Symmentioning
confidence: 99%